"What Don't We Do?": The Experiences of School Counseling Directors in Relation to Leadership and Job Satisfaction. Issue 1 (January 2019) - Walsh, Robyn; Gibson, Donna M.
Limited research has explored the experiences of school counseling directors, defined in this study as school counselors who are the designated department leaders and school counseling supervisors at middle or high schools. In this phenomenological study, we sought to better understand the experiences of those directors, specifically in relation to leadership and job satisfaction. Four themes emerged from the data collected from the 10 participants. We discuss these themes and offer implications for training, support, and role clarification for school counseling directors.